PERUBAHAN PENGELOLA DTW TANAH LOT DAN DAMPAKNYA TERHADAP MASYARAKAT LOKAL - Krisna Arta Widana, I Putu (Jurnal Master Pariwisata (JUMPA); Volume 02, Nomor 02, Januari 2016DO - 10.24843/JUMPA.2016.v02.i02.p02)
This article discusses the impact of the management changes of Tanah Lot tourist attraction on community of Beraban village, Tabanan, Bali, and efforts of the new management in realizing Tanah Lot as a sustainable tourist attraction. The research method used is a qualitative method with data collection techniques, namely observation, interviews, and documentation. The management changes of Tanah Lot tourist attraction have direct and indirect impacts to the local community. The impacts are divided into three aspects, namely physical, social cultural and economic aspect. Efforts made by the new management in order to realize Tanah Lot includes adding tourist attractions, tourism facilities, distributes the location of trade, organising and supervising activities of the tourism business, and forming a group of merchants as well as establishing good relationship and communication with private land owner. Indicators used as a benchmark is the Magic Pentagon, namely a healthy economy,the welfare of the local community, does not change the natural, healthy culture, and tourist satisfaction.
Keywords: management changes, the impact of management changes, sustainable tourism, Tanah Lot tourist attraction